Sustainable Land Management and Ecosystem Services in Agroforestry Systems - Quevedo, Jay Mar D.; Tamura, Norie; Uchiyama, Yuta; Kohsaka, Ryo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on case studies and theoretical concepts on sustainable land-use management in agroforestry systems. Special attention is given to farmland management in the contexts of farmers' investments, farmers' economic and behavioral factors, and farmers' perceptions of irrigation systems. Urban agriculture and its extensions (e.g., urban gardening and urban beekeeping) are also featured in this book, in addition to the ways in which these practices can contribute to biodiversity conservation goals. Additionally, a case study on the use of the ecosystem evaluation index is featured and provides scientific and practical bases for land protection. Lastly, a state-of-the-art review on land-use policy is included, providing insights into how agroforestry systems can be converted to other land uses to meet the current demands. Scientists, practitioners, and policymakers can make use of this book in designing sustainable agroforestry systems.